1998
DOI: 10.1590/s0100-06831998000200007
|View full text |Cite
|
Sign up to set email alerts
|

Adsorção de fósforo e sua relação com formas de ferro em dez solos do Uruguai

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
6
0
7
Order By: Relevance
“…Unlike the P-rem, the clay contents moderately correlated only with the Fe DCB (r = 0.66 ** ) ( Table 3). The lack of correlation between the clay content and Fe OX is an indication that soil clay accumulation is not necessarily associated with the presence of Fe oxides of low crystallinity, which are described as having a high capacity of P adsorption (Hernández and Meurer, 1998;Donagemma et al, 2008). In addition to crystalline Fe oxides and clay minerals 1:1 (such as kaolinite), which have a lower potential to adsorb Fe oxides of low crystallinity, they can also significantly affect the adsorption of P, mainly due to the higher quantity generally found in soils (Torrent et al, 1994;Vilar et al, 2010).…”
Section: Relationship Between the Physical And Chemical Properties Ofmentioning
confidence: 99%
“…Unlike the P-rem, the clay contents moderately correlated only with the Fe DCB (r = 0.66 ** ) ( Table 3). The lack of correlation between the clay content and Fe OX is an indication that soil clay accumulation is not necessarily associated with the presence of Fe oxides of low crystallinity, which are described as having a high capacity of P adsorption (Hernández and Meurer, 1998;Donagemma et al, 2008). In addition to crystalline Fe oxides and clay minerals 1:1 (such as kaolinite), which have a lower potential to adsorb Fe oxides of low crystallinity, they can also significantly affect the adsorption of P, mainly due to the higher quantity generally found in soils (Torrent et al, 1994;Vilar et al, 2010).…”
Section: Relationship Between the Physical And Chemical Properties Ofmentioning
confidence: 99%
“…Under conditions of greater water availability, dissolution and remobilization mechanisms of Fe come into action, which include reduction and complexation reactions (Schwertmann, 1991), favoring its greater concentration and leaching in soils with a low level of clay. In a study carried out by Hernández and Meurer (1998) in 10 soils of Uruguay, subject to temporal variations in oxidation-reduction conditions, it was observed that soil with low clay contents (cretaceous sandstones) exhibited lower Fe content, and a correlation was observed between Fe contents and clay contents of the soils. In a study evaluating eight soil samples from the provinces of Antwerp and West-Flanders in Belgium with known micronutrient and heavy metal values, and subjected to the treatments of dry soil, soil at field capacity, and saturated soil, Tack et al (2006) observed that the events of wetting and drying of the soil changed the hydration, oxidation, and crystallinity status of the Fe and Mg oxides of the soil, favoring the release of these elements under wetter environments.…”
Section: Soilmentioning
confidence: 99%
“…Muitos trabalhos na literatura indicaram os óxidos de Fe como os principais participantes na elevada CMAP dos solos (Hernández & Meurer, 1998); todavia, os resultados do presente estudo revelam que a fração argila livre dos óxidos de Fe pode também contribuir de maneira significativa para a adsorção de P (Figura 2). O efeito de cimentação e de recobrimento que os óxidos de Fe e a matéria orgânica exercem sobre os demais componentes da fração argila dos solos pode impedir que eles manifestem sua atividade de superfície (Souza Junior et al, 2007) e do Al presente nas entrecamadas dos minerais de argila do tipo 2:1, que podem adsorver grande quantidade de P (Karathanasis & Shumaker, 2009).…”
Section: Relações Entre a Cmap E Os Atributos Mineralógicos Dos Solosunclassified
“…Isso ocorre em razão da maior densidade de sítios ácidos de Lewis (Novais & Smyth, 1999) na superfície dos coloides. Na fração argila natural, os teores de Fe e Al extraídos por ditionito-citrato-bicarbonato de sódio (Fe d e Al d , teor livre) e oxalato ácido de amônio a pH 3 no escuro (Fe o e Al o , teor pobremente cristalino) são alguns dos atributos mineralógicos que melhor se correlacionam com a CMAP (Hernández & Meurer, 1998). Com muita frequência, a correlação com os teores pobremente cristalinos tem sido maior do que com os teores livres (Hernández & Meurer, 1998).…”
Section: Introductionunclassified
See 1 more Smart Citation